Hubungan antara Bauran Pemasaran Kecap Bango dan Keputusan Pembelian pada Generasi Millenial di Kota Denpasar - KUMIL LAILA; NYOMAN PARINING; IGAA LIES ANGGRENI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
The Relation between Bango Soy Sauce Marketing Mix and Purchase Decisions onMillennials Generation in Denpasar City Increasing the soy sauce business every year causes intense competition by producers,including Unilever with its flagship soy sauce product Bango. In recent years, thenumber of Bango ketchup consumers in the millennium is less than that of generationX. Consumer decisions in the purchase of Kecap Bango in the millennium areinfluenced by many factors, one of which is the marketing mix elements.This researchwas conducted by 100 millennial generation respondents in Denpasar City who aimed tofind out the dominant marketing mix elements considered by the millennium generationin buying Bango soy sauce in Denpasar City and analyze the relationship between themarketing mix and purchasing decisions. This research used accidental samplingtechnique with purposive sampling method and analyzed using Rank Spearmancorrelation. The results of this study indicate that the distribution is an element of themarketing mix which is most dominantly considered by the millennial generation inbuying Bango soy sauce. Marketing mix elements that have a significant relationshipwith purchasing decisions are product and distribution.Producers are expected tocontinue to maintain and even develop product quality, diverse features and attractivedesigns so that consumers still trust the product and the marketing target of Bango soysauce is achieved. In addition, producers are expected to maintain and even expanddistribution channels so that consumers can easily get Bango soy sauce and will notmove to other brands.